Peran Sistem Informasi Pemasaran dalam Mengelola Proses Pemasaran Melalui Digital Marketing - Aldina Esty Purwanti; Feri Lupiana (Universitas Sains dan Teknologi Komputer, 2023)
Marketing information systems are not new, their scale, scope and functionality have grown due to the substantial growth of new technologies such as the internet, mobile devices and social media. Communication in digital marketing requires interaction between consumers and brands so that the need for product campaigns and communication can run more efficiently. Intense interactions through online channels allow brands to reach a wider audience. This study aims to examine the impact of implementing a Marketing Information System (SIP) by the marketing department in managing marketing business processes in multinational companies in Indonesia. The subject of this research involves 3 large companies in Indonesia that have succeeded in implementing the Cloud Marketing platform in their marketing business processes. Structured interviews and distribution of questionnaires via e-mail were conducted to collect data that was analyzed with the Leximancer 4.5 platform which supports finding relationships between words in text analysis. The results of the analysis found relevant relationships related to the analysis of benefits and quality of services, information and systems.